Strategi Pemasaran Emping Melinjo Oleh Masyarakat Desa Padang Burnai Kecamatan Muara Pinang Kabupaten Empat Lawang - Agnes , Masayu; Murdiati , Eni; Muslimin, Muslimin (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Indonesia is rich in plants and fruits of various kinds including melinjo fruit, this fruit is one of the fruits that can be processed into chips. The thesis entitled Marketing Strategy for Emping Melinjo by the Community of Padang Burnai Village, Muara Pinang District, Empat Lawang Regency. This research aims to find out what the marketing strategy for emping melinjo is in Padang Burnai village, the marketing strategy used by researchers from product, price, place and promotion as well as the processing process in making emping melinjo. Emping melinjo which is found in the Padang Burnai area has not been created yet so it still has the original taste without additives such as flavorings or coloring. It is hoped that the people who are engaged in the melinjo chip business in Padang Burnai Village can further develop and innovate again to advance the economy of the Padang Burnai village and to become more familiar with a more modern sales system, and the method used in this research is descriptive qualitative. The type of data used is primary and secondary data. The data collection technique used in this study was carried out using observation, interview and documentation techniques. The results obtained in this study, researchers can find out what strategies can be used to increase sales in a good business, and can get to know more about how modern work systems make it easier for sellers to process.